IDENTIFIKASI KESULITAN MAHASISWA DALAM PEMBELAJARAN BIOLOGI MOLEKULER BERSTRATEGI MODIFIED FREE INQUIRY: (Identification of Student Difficulties in Molecular Biology with Modified Free Inquiry Learning Strategy) - Evi Suryanti; Any Fitriani; Sri Redjeki; Riandi Riandi (UIR Press, 2019)
The aim of this study was to identify the difficulties learning by students in the modified free inquiry learning strategy of Molecular Biology and the causes of these difficulties. The method used is descriptive with a questionnaire technique. Respondents are 51 Biology Education students who contracted the Molecular Biology course in Academic Year 2017/2018 at one of the education institution in Kota Pekanbaru. The stages in the modified free inquiry strategy that are carried out consist of steps: 1) orienting students to the topics discussed by giving direct questions, 2) students make questions as the formulation of the problem, 3) proposing hypotheses, 4) collecting data and information for testing hypotheses, 5) communicating findings, and 6) concluding. Topics covered were DNA isolation, agarose gel electrophoresis, and polymerase chain reaction (PCR) and in the lectures were complemented by wet and virtual laboratory activities. Research instruments in the form of a closed questionnaire with answer choices 'yes' and 'no'. Data analyzed are presented in the form of percentage figures. The results of data analysis showed that: (1) Students who experienced difficulty in learning Molecular Biology with a modified free inquiry strategy were 45.10% and those who did not experience difficulties were 54.90%; (2) The causes of difficulties are limited time (78.26%), not finding adequate learning resource materials (39.13%), unable to understand the learning resource materials found (39.13%), unable looking for adequate learning resource materials (21.74%), and not interested in the modified free inquiry strategy (17.39%); and (3) most students agree to apply the modified free inquiry strategy to other biology courses. The implication of the research is the modified free inquiry strategy can be applied in biology learning at the university level.